Dendrite-Free and Stable Lithium Metal Battery Achieved by a Model of Stepwise Lithium Deposition and Stripping - Liu, Tiancun; Wang, Jinlong; Xu, Yi; Zhang, Yifan; Wang, Yong (Nano-Micro Letters, 2021)
The uncontrolled formation of lithium (Li) dendrites and the unnecessary consumption of electrolyte during the Li plating/stripping process have been major obstacles in developing safe and stable Li metal batteries. Herein, we report a cucumber-like lithiophilic composite skeleton (CLCS) fabricated through a facile oxidation-immersion-reduction method. The stepwise Li deposition and stripping, determined using in situ Raman spectra during the galvanostatic Li charging/discharging process, promote the formation of a dendrite-free Li metal anode. Furthermore, numerous pyridinic N, pyrrolic N, and CuxN sites with excellent lithiophilicity work synergistically to distribute Li ions and suppress the formation of Li dendrites. Owing to these advantages, cells based on CLCS exhibit a high Coulombic efficiency of 97.3% for 700 cycles and an improved lifespan of 2000 h for symmetric cells. The full cells assembled with LiFePO4 (LFP), SeS2 cathodes and CLCS@Li anodes demonstrate high capacities of 110.1 mAh g−1 after 600 cycles at 0.2 A g−1 in CLCS@Li|LFP and 491.8 mAh g−1 after 500 cycles at 1 A g−1 in CLCS@Li|SeS2. The unique design of CLCS may accelerate the application of Li metal anodes in commercial Li metal batteries. Highlights: 1 A facile method is adopted to obtain cucumber-like lithiophilic composite skeleton. 2 Massive lithiophilic sites in cucumber-like lithiophilic composite skeleton can promote and guide uniform Li depositions. 3 A unique model of stepwise Li deposition and stripping is determined.